Modern Trends in the Development of the Human Resource Management System - Adilov Botir Baltabaevich; Ochilov Sardor Xayitboy o’g’li (Researchparks Publishing, 2022)
The article discusses modern HR technologies necessary for the strategic management of domestic companies, as well as the main difficulties and problems associated with accounting, control and motivation of personnel. It reflects in detail how the specificity of HR management is manifested, together with approaches to building the functions of the personnel management process. The mechanisms for improving HR management in the business environment and the role of consulting agencies in recruiting are disclosed in detail. The conclusion is made about the existence of a number of contradictions and conflict situations in the process of HR-specialists' activity in the modern labor market.